Asimov: Um Laboratório Remoto para Ensino Experimental de Robótica - Gustavo Yoshio Maruyama (2024)
This article addresses the development, testing and evaluation of the Asimov - Remote Robotics Laboratory system. It is a remote experimentation environment that allows people, anywhere in the world, to carry out practical programming experiments on robots or microcontrolled devices remotely. The system was tested in practice through the application of a basic programming and robotics course entirely remotely in an asynchronous format, where the practical part took place through the developed system. Finally, a usability evaluation of the system was carried out based on the user's perception regarding usefulness, ease of use, graphical interface and teaching.